Analisis Faktor Penentu Ekspor Kopi di Indonesia - Heppi Syofya; Enang Dwisefianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
International trade includes export and import activities that take place globally between countries. Export is the act of selling goods abroad to generate more foreign exchange for a country. When a country has excess income, it can engage in export-related activities. Indonesia is the fourth largest coffee producer in the world, and is an important contributor to the country's economy. Indonesian coffee is also one of the most popular in the world, and is one of Indonesia's main agricultural export commodities, besides oil and gas. This study aims to see if there is a significant impact through production variables, land area, exchange rates, inflation, prices, consumption on the volume of coffee exports. For this study, the data collection used is secondary data, where secondary data is obtained through the central statistics agency and BI. The data analysis method is used to calculate all data that has been obtained using multiple linear regression analysis with the help of SPSS. The results of this study are that simultaneously production, land area, exchange rates, prices, consumption affect the volume of Indonesian coffee exports. While the inflation variable does not affect exports in Indonesia.